2016
DOI: 10.1002/hep.28685
|View full text |Cite
|
Sign up to set email alerts
|

Lack of immunological DNA sensing in hepatocytes facilitates hepatitis B virus infection

Abstract: Hepatitis B virus (HBV) is a major human pathogen, and about one third of the global population will be exposed to the virus in their lifetime. HBV infects hepatocytes, where it replicates its DNA and infection can lead to acute and chronic hepatitis with a high risk of liver cirrhosis and hepatocellular carcinoma. Despite this, there is limited understanding of how HBV establishes chronic infections. In recent years it has emerged that foreign DNA potently stimulates the innate immune response, particularly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
134
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(145 citation statements)
references
References 46 publications
11
134
0
Order By: Relevance
“…Notably, all PHH samples had very low sequence counts (range: 0–30 counts from ~30 million total reads per sample) of STING ( TMEM173 ), an adaptor protein of an innate immune receptor (cGAS) that senses intracellular DNA. This is consistent with a recent study which reported that neither murine or human hepatocytes express STING [33]. …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Notably, all PHH samples had very low sequence counts (range: 0–30 counts from ~30 million total reads per sample) of STING ( TMEM173 ), an adaptor protein of an innate immune receptor (cGAS) that senses intracellular DNA. This is consistent with a recent study which reported that neither murine or human hepatocytes express STING [33]. …”
Section: Resultssupporting
confidence: 94%
“…While our data does not directly address these two possibilities, it is striking that we were not able to detect an innate immune response in PHH at any time post-infection with HBV or HBVΔX. Moreover, we detected little to no STING expression in PHH, consistent with a recent study which reported that deficiency of this adaptor protein prevents functional DNA sensing in hepatocytes, thereby facilitating HBV infection [33]. …”
Section: Discussionsupporting
confidence: 91%
“…We used the embryonically-derived murine hepatocyte cell line, TIB73, because RECON is highly expressed in hepatocytes, and mice with obstructed NF-κB activation specifically in hepatocytes are unable to clear Lm , even in the presence of NF-κB-competent immune cells (Lavon et al, 2000). Additionally, a recent study has shown that primary human and murine hepatocytes do not express STING (Thomsen et al, 2016), therefore the use of this cell type would allow us to study NF-κB activation without complications from IFN feedback.…”
Section: Resultsmentioning
confidence: 99%
“…also showed that overexpression of MITA/STING in mice hepatocytes could reduce HBV replication. However, they found that MITA/STING deficiency has no influence on HBV replication in a adenovirus-HBV model [55]. The discrepancy may attribute to the different mechanisms of host recognition and responses to systemic infected adenovirus vector and naked plasmid DNA delivered by HI.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that cGAS/STING pathway was essential in MyD88-independent pathway for type I IFN induction and antiviral response to recombinant adenovirus (rAdV). Although the rAdV could trigger robust type I IFN production through STING-IRF3 pathway as well as Ad-HBV proved by Thomsen [55], loss of cGAS/STING minimally impacted viral clearance and persistence of transgene expression delivered by rAdV [57], which indicated that cGAS/STING was dispensable to the induction of adaptive immune response to rAdV. The minimal impact of MTIA/STING-mediated type I IFN pathway on adaptive immune response to rAdV was also previously confirmed in STAT2 knockout Syrian hamster model and IFNRI and STING knock out mouse [58, 59].…”
Section: Discussionmentioning
confidence: 99%